Adverbs and Adverbials Categorial Issues. - Duplâtre, Olivier; Modicom, Pierre-Yves (Trends in Linguistics. Studies and Monographs [TiLSM] ;, 2022)
Adverbs seem to raise unsolvable issues for theories of word-classes, both crosslinguistically and language-internally. The contributions in this volume all address this categorial problem from a variety of formal and functional points of view. In the first part, current definitions of the class for Romance and Germanic languages are being questioned and improved, drawing on data from English, German and Italian. The second part is devoted to adverbial scope in Romance (French, Italian and Brazilian Portuguese), Germanic, Modern Greek and Chinese, under special consideration of modal adverbs, subject-oriented manner adverbs and domain adverbs and adverbials. Syntactic and semantic relationships appear to lay the ground for a robust and fine-grained functional definition of adverbs and adverbials.